The strategic management of international manufacturing and sourcing - Sweeney, Mike T. (Cranfield University, 1993)
Little previous research has been carried out on the strategic management of international manufacturing and the subject appearsto be a “missing theme” in operations management literature. What are the criteria used for the selection of products to be manufactured offshore, what are they for sourcing from third parties or for manufacturing in the home country? This is the subject of this paper. The research tindings show the hypothesis that offshore manufacturing is organized to prolong the competitivenessof mature products to be an oversimplification as an explanation for the location of production. Some manufacturing businessesnow use time based competitive strategies and their take-up requires a different configuration of manufacturing resources.